Potential of Reinforced Indonesian Glulam Beams Using Grade I (Bengkirai), Grade II (Kamper), Grade III (Nyatoh) Woods for Use in Structural Wood Design - Saptahari Sugiri; Eka Mulya Alamsyah; Arie Putra Usman (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Wood is a natural resource that is renewable and available in various species in tropical countries. Its abundancy in nature makes it easy to obtain, thus making it a nature friendly material for use in construction. Indonesia is the most important source of tropical wood in the world after Brazil, making the use of wood for structural elements very desirable. It is estimated that 4000 different varieties of wood exist in Indonesia. This estimate is based on the herbarium species collected by the Forestry Research Institute, currently counting nearly 4000 types of trees with a diameter of more than 40 cm. In the Indonesian wood structure code, the strength of woods is divided into 3 grades (grade I, II and III). This paper presents an evaluation of the mechanical properties of glulam wood sourced from native Indonesian timber: Bengkirai wood (grade I), Kamper wood (grade II), and Nyatoh wood (grade III), thus proving the potential for Indonesian wood as industrial structural elements in wooden constructions.